The Comparison of Plasma and Cerebrospinal Fluid R(−)- and S(+)-Flurbiprofen Concentration After Intravenous Injection of Flurbiprofen Axetil in Human Subjects - Yao, Han; Luo, Xingxian; Zhang, Hong; An, Haiyan; Feng, Wanyu; Feng, Yi (Frontiers in pharmacology, 2021)
Background: Flurbiprofen axetil is a prodrug that releases the active substance through enzymatic removal of the ester moiety. It is formulated through encapsulation in a lipid microsphere carrier, and widely used to treat perioperative pain. Here, we studied the distribution of R (−)- and S (+)-flurbiprofen in human plasma and cerebrospinal fluid (CSF) after intravenous injection of flurbiprofen axetil. Methods: A total of 70 adult patients undergoing elective lower limb surgery under spinal anesthesia were given a single intravenous injection of 100-mg flurbiprofen axetil. The patients were randomly assigned to 10 groups for plasma and CSF sampling at 10 time points (5–50 min) after subarachnoid puncture and before actual spinal anesthesia. R (−)- and S (+)-flurbiprofen and CSF/plasma ratio were determined by liquid chromatography–tandem mass spectrometry. Results: R (−)-flurbiprofen concentration ranged from 2.01 to 10.9 μg/mL in plasma and 1.46–34.4 ng/mL in CSF. S (+)-flurbiprofen concentration ranged from 1.18 to 10.8 μg/mL in plasma and from 2.53 to 47 ng/mL in CSF. In comparison to S (+)-flurbiprofen, R (−)-flurbiprofen concentration was significantly higher in plasma at all time points ( p < 0.05) except at 30 or 40 min, and lower in CSF at all time points ( p < 0.05) except at 10, 15 and 40 min. Analysis after correcting drug concentration for body mass index also revealed higher plasma and lower CSF R (−)-flurbiprofen concentration. In comparison to S (+)-flurbiprofen, AUC 0–50 for R (−)-flurbiprofen was larger in plasma and smaller in CSF ( p < 0.05 for both), and accordingly smaller CSF/plasma AUC 0–50 ratio ( p < 0.05). There was a positive correlation between R (−)-flurbiprofen concentration and S (+)-flurbiprofen concentration in plasma (r = 0.725, p < 0.001) as well as in CSF (r = 0.718, p < 0.001), and a negative correlation between plasma and CSF concentration of S (+)-flurbiprofen (r = −0.250, p = 0.037), but not R (−)-flurbiprofen. Conclusion: Distribution of R (−)- and S (+)-flurbiprofen in plasma and CSF differed significantly. Penetration of R (−)-flurbiprofen into the CNS was lower than S (+)-flurbiprofen.